2018
DOI: 10.1093/cid/ciy103
|View full text |Cite
|
Sign up to set email alerts
|

High Proportions of Patients With Advanced HIV Are Antiretroviral Therapy Experienced: Hospitalization Outcomes From 2 Sub-Saharan African Sites

Abstract: BackgroundHuman immunodeficiency virus (HIV) remains an important cause of hospitalization and death in low- and middle- income countries. Yet morbidity and in-hospital mortality patterns remain poorly characterized, with prior antiretroviral therapy (ART) exposure and treatment failure status largely unknown.MethodsWe studied HIV-infected inpatients aged ≥13 years from cohorts in Kenya and the Democratic Republic of Congo (DRC), assessing clinical and demographic characteristics and hospitalization outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 16 publications
10
66
1
Order By: Relevance
“…In South Africa, 56.7% of patients entering care in 2017 with very advanced HIV disease were treatment experienced (20). The prevalence of advanced HIV disease was lower in the current study than reported in the literature [18][19][20][21]; however, this could have been due to the variable uses of CD4 testing across included countries within the current study. During the study period, CD4 was still used to monitor treatment as access to viral load testing was significantly below coverage rates in South Africa [5].…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…In South Africa, 56.7% of patients entering care in 2017 with very advanced HIV disease were treatment experienced (20). The prevalence of advanced HIV disease was lower in the current study than reported in the literature [18][19][20][21]; however, this could have been due to the variable uses of CD4 testing across included countries within the current study. During the study period, CD4 was still used to monitor treatment as access to viral load testing was significantly below coverage rates in South Africa [5].…”
Section: Resultscontrasting
confidence: 73%
“…Further, reviewing CD4 data in nearly one million patients attending health care facilities within the IeDEA and COHERE cohorts across 55 countries found that not only has the proportion of patients entering care remained high across settings (31% in low-income countries, 40% in low-and middle-income countries, 29% in high-income countries), but these rates have plateaued over the past few years [19]. Interestingly, many patients entering, or re-entering care, are treatment experienced [20,21]. In South Africa, 56.7% of patients entering care in 2017 with very advanced HIV disease were treatment experienced (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a higher CD4 was associated with a reduced risk of attrition from care, which is similar to findings from other studies . Those with lower CD4 cell counts are more likely to be lost to programme because of increased mortality . Similar to Mugglin et al .…”
Section: Discussionsupporting
confidence: 90%
“…In 28 studies with details on ART status, 26% (1792/6777) had a history of current or previous ART use. Reasons for exclusion are detailed in Appendix S1; these included non-representative sampling [24,[75][76][77], high loss to follow-up or duration of follow-up not clear [62,78], antifungal treatment not available [23,79,80] and use of treatment regimens not used or contraindicated in management [81][82][83].…”
Section: Overall Search Findingsmentioning
confidence: 99%